Long-Term Test-Retest Reliability of Auditory Gamma Oscillations Between Different Clinical EEG Systems - Hirano, Yoji; Nakamura, Itta; Tamura, Shunsuke; Onitsuka, Toshiaki (Frontiers in Psychiatry, 2020)
Objective: There is increasing interest in the utility of gamma-band activity for assessing various brain functions, including perception, language, memory, and cognition. The auditory steady-state response (ASSR) involves neural activity in the brain elicited by trains of a click sound, and its maximum response is obtained at 40-Hz (40-Hz ASSR). Abnormalities of the 40-Hz ASSR are also widely reported in patients with schizophrenia. Thus, the test-retest reliability of the ASSR is important for its clinical and translational application. However, there are only limited studies reporting the short-term reliability between acquisitions at two time-points made using the same electroencephalograph (EEG) system. Furthermore, the long-term reliability between multiple EEG systems and the reliability of spontaneous gamma activity are unknown, but are crucial for multicenter collaborative research. Methods: We examined the long-term test-retest reliability of 40-Hz ASSR oscillatory activities indexed by the phase-locking factor (PLF), evoked power, and (non-phase-locked) induced power between two clinical 19-electrode EEG systems (recorded twice for EEG-1 [time1 and time2] and EEG-2 [time3 and time4]) at four time-points from 14 healthy controls over a duration of 5 months. Test-retest reliability was examined using intraclass correlation coefficients (ICCs). Results: Both PLF and evoked power showed good to excellent ICCs (>0.60), mainly in the Fz-electrode, both within each EEG system—EEG-1 ([time1 vs time2] PLF: ICC=0.66, evoked power: ICC=0.88) and EEG-2 ([time3 vs time4] PLF: ICC=0.82, evoked power: ICC=0.77)—and between the two EEG systems ([EEG-1 vs EEG-2] PLF: ICC=0.73, evoked power: ICC=0.84). In contrast, induced power showed the highest (excellent) ICC between the two EEG systems (ICC=0.95) mainly in the Cz-electrode. For PLF, the Fz-electrode showed better test-retest reliability across all EEG recordings than the Cz-electrode (Fz: ICC=0.67, Cz: ICC=0.63), whereas we found similar excellent reproducibility across all EEG recordings from both electrodes for evoked power (Fz: ICC=0.79, Cz: ICC=0.77) and induced power (Fz: ICC=0.79, Cz: ICC=0.80). Conclusion: The 40-Hz ASSR oscillatory activities, including induced power, showed excellent test-retest reliability, even when using different EEG systems over a duration of 5 months. These findings confirm the utility of the 40-Hz ASSR as a reliable clinical and translatable biomarker for multicenter collaborative research.